Peculiarities of identifying steadiness characteristics of the cutting lettuce (Lactuca sativa L.) to the false powdery mildew (Bremia lactucae Regel) - А. В. Андрющенко; Н. В. Лещук; Н. В. Шовгун (Plant Varieties Studying and Protection)
In the article the recommendations of UPOV concerning identifying of varieties of cutting lettuce in the characteristic of steadiness to the powdery mildew (Bremia lactucae Regel) using assessment of the reaction of each specific feature of the famous virulent Dm component or those, which have in their genic structure, at leaset Dm genes, that further the defining of famous and non famous, present or absent Dm genes at the moment of variety identification. The nomenclature system of Dm genes is considered to be international for the description of cutting lettuce varieties Dm genes components.